PERSEPSI PEDAGANG KAKI LIMA TERHADAP PENERTIBAN LOKASI PASAR SIMPANG PADANG DURI DI KECAMATAN MANDAU KABUPATEN BENGKALIS - Darnawita, Yatni; ", Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Street vendors (PKL) is one of the informal sectors that emerged in urban areas. Street vendors as one example of the informal sector has the potential as employment that can absorb labor, especially in workers who have low education and do not have the ability and expertise sufficient to be able to work in the formal sector. Street vendors usually use carts or stalls that are located in places that are considered strategic. Street vendors are famous for their existence who use public space as a place to trade. The increasing number of street vendors is caused by the free opportunity for anyone to trade and the lack of jobs. By utilizing public spaces such as sidewalks to the shoulder of the road causing problems for smooth traffic. The Local Government of Bengkalis Regency has overcome this problem by curbing the street vendors who occupy the sidewalks and the shoulder of the road as a place to trade. disciplined traders are traders who use shanties in the form of tables and mats used as a place to place their wares. The theory used in this research is perception theory. This research is a descriptive quantitative research. The population of this study were all street vendors affected by the government policing targets, while the sample in this study was 50% of the total population. Data collection is done by observation, interviews after preparing a list of questions or questionnaires, and documentation. The results of this study can be concluded that the perception of traders of controlling the location of the Padang Duri Simpang Market is a positive perception with the amount of 58,8% and negative 41,2% . While the factors that influence it are knowledge, socialization, and experience.Keywords: Perception, Control of Street Vendors at Padang Duri Simpang Market